Comparative bioinformatics analysis and abiotic stress responses of expansin proteins in Cucurbitaceae members: watermelon and melon - İncili, Çınar Yiğit; Arslan, Büşra; Çelik, Esra Nurten Yer; Ulu, Ferhat; Horuz, Erdoğan; Baloglu, Mehmet Cengiz; Çağlıyan, Ebrar; Burcu, Gamze; Bayarslan, Aslı Ugurlu; Altunoglu, Yasemin Celik (Springer Science and Business Media LLC, 2022)
Watermelon and melon are members of the Cucurbitaceae family including economically significant crops in the world. The expansin protein family, which is one of the members of the cell wall, breaks down the non-covalent bonds between cell wall polysaccharides, causing pressure-dependent cell expansion. Comparative bioinformatics and molecular characterization analysis of the expansin protein family were carried out in the watermelon (Citrullus lanatus) and melon (Cucumis melo) plants in the study. Gene expression levels of expansin family members were analyzed in leaf and root tissues of watermelon and melon under ABA, drought, heat, cold, and salt stress conditions by quantitative real-time PCR analysis. After comprehensive searches, 40 expansin proteins (22 ClaEXPA, 14 ClaEXPLA, and 4 ClaEXPB) in watermelon and 43 expansin proteins (19 CmEXPA, 15 CmEXPLA, 3 CmEXPB, and 6 CmEXPLB) in melon were identified. The greatest orthologous genes were identified with soybean expansin genes for watermelon and melon. However, the latest divergence time between orthologous genes was determined with poplar expansin genes for watermelon and melon expansin genes. ClaEXPA-04, ClaEXPA-09, ClaEXPB-01, ClaEXPB-03, and ClaEXPLA-13 genes in watermelon and CmEXPA-12, CmEXPA-10, and CmEXPLA-01 genes in melon can be involved in tissue development and abiotic stress response of the plant. The current study combining bioinformatics and experimental analysis can provide a detailed characterization of the expansin superfamily which has roles in growth and reaction to the stress of the plant. The study ensures detailed data for future studies examining gene functions including the roles in plant growth and stress conditions.
Keywords: Citrullus; Cucurbitaceae; Stress, Physiological; Gene Expression Regulation, Plant; Proteins; Computational Biology; 2. Zero hunger